The Influence of Digital Information Quality, Brand Trust, Digital Service Quality, and Ease of Access Digital to Customer Satisfaction PT Pintu Berkat Bahagia Jakarta - Imam Suryono; Putri Sara Sabila (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The rapid growth of digital commerce has transformed customer behavior, including in the luxury retail sector. Customers increasingly rely on digital platforms to access product information, interact with sellers, and conduct transactions. However, in luxury retail, where product authenticity, service quality, and trust are crucial, maintaining customer satisfaction through digital channels becomes a strategic challenge. Previous studies highlight the role of information quality, trust, service quality, and ease of access in shaping customer satisfaction in digital environments. This study aims to analyze the influence of digital information quality, brand trust, digital service quality, and digital accessibility on customer satisfaction at PT. Pintu Berkat Bahagia Jakarta, both partially and simultaneously. This research uses a quantitative associative approach. The sample consists of 128 reseller customers selected through purposive sampling from a population of 189 customers. Data were collected using a structured questionnaire with a Likert scale (1–5). Analysis techniques include validity and reliability tests, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination (R²). The results show that digital information quality, brand trust, digital service quality, and digital accessibility each have a positive and significant effect on customer satisfaction. Simultaneously, these variables explain 84.8% of the variation in customer satisfaction, indicating that integrated digital service management is a key factor in improving satisfaction. This study contributes to digital marketing and customer satisfaction literature by confirming that customer satisfaction in luxury digital retail is shaped by multiple service-related factors. Practically, the findings provide guidance for companies to enhance digital information accuracy, strengthen trust, This study focuses on a single company and reseller customers only, which may limit generalization. Future research may include broader customer segments and additional variables such as customer loyalty or brand value